Leveraging User Experience through Input Style Transformation to Improve Access to Music Search Services - Purgina, M.; Kuznetsov, A.; Pyshkin, E. (Informatica, 2014)
Leveraging User Experience through Input Style Transformation to Improve Access to Music Search Services